Fatigue in Liver Disease: Pathophysiology and Clinical Management - Mark G Swain (Canadian Journal of Gastroenterology)
Fatigue is the most commonly encountered symptom in patients with liver disease, and it has a significant impact on their quality of life. However, although some progress has been made with regard to the understanding of the processes which may generate fatigue in general, the underlying cause(s) of liver disease-associated fatigue remain incompletely understood. The present review describes recent advances which have been made in our ability to measure fatigue in patients with liver disease in the clinical setting, as well as in our understanding of potential pathways which are likely important in the pathogenesis of fatigue associated with liver disease. Specifically, experimental findings suggest that fatigue associated with liver disease likely occurs as a result of changes in neurotransmission within the brain. In conclusion, a reasonable approach to help guide in the management of the fatigued patient with liver disease is presented.